15-Deoxyspergualin and cyclophosphamide, but not mycophenolate mofetil, prolong survival and attenuate renal disease in a murine model of ANCA-associated crescentic nephritis - Birck, Rainer; Newman, Mark; Braun, Claude; Neumann, Irmgard; Nemoto, Kyuichi; Yard, Benito A.; Waldherr, Rüdiger; Woude, Fokko J. van der (Nephrology, dialysis, transplantation, 2006)
BACKGROUND: Here we compare the efficacy of cyclophosphamide (CYC) for treatment of crescentic nephritis (CGN) with the newer immunosuppressants 15-deoxyspergualin (DSG) and mycophenolate mofetil (MMF) in SCG/Kj mice, an inbred mouse strain that spontaneously develops CGN, systemic necrotizing vasculitis and antineutrophil cytoplasmic antibodies (ANCAs). METHODS: Mice were randomly assigned to intraperitoneal treatment with either DSG (2 mg/kg/day), CYC (50 mg/kg/week), MMF (60 or 100 mg/kg/day) or vehicle (VEH, dextrose 5% 0.3 ml/day) beginning at the 10th week of life. ANCA, blood urea nitrogen (BUN) and proteinuria were determined in all animals regularly, and survival was calculated. Renal histology was obtained in the 18th week of life in the MMF- or VEH-treated groups and in the 24th week in DSG- or CYC-treated animals. RESULTS: Mean survival in VEH-treated animals was 123 days. At that point, survival was 100% in the CYC- or DSG-treated animals (P<0.001). Survival in the MMF group (pooled data) was not significantly different from the VEH-treated animals [MMF, 117 days (95% CI 108-127)]. BUN (18th week, CYC 43+/-9 mg/dl and DSG 36+/-6 mg/dl vs VEH 73+/-28 mg/dl, P<0.001, MMF 66+/-26 mg/dl), 24 h proteinuria (18th week, CYC 0.4+/-0.2 mg and DSG 0.7+/-0.6 mg vs VEH 2.7+/-3 mg, P<0.001, MMF 2.2+/-3 mg) crescent formation (18th week, VEH 42+/-9%, MMF 39+/-11%; CYC 5+/-2% and DSG 22+/-7% vs VEH, P<0.05), glomerular immune complex deposition, and ANCA formation were significantly improved in CYC- and DSG- but not in MMF-treated animals when compared with controls. CONCLUSION: DSG and CYC, but not MMF, prolong life, limit renal damage and prevent autoantibody formation in SCG/Kj mice.
Advance Access publication 2 September 2005
Gesehen am 24.05.2022